Diagnosing the Level of Forming the Practical Component of Future Physical Education and Sports Specialists’ Readiness for Educational Activities to achieve Sustainable Development - Tsyhura, Halyna; Harkusha, Serhii (Physical Education Theory and Methodology, 2024)
Background. Ukraine’s support for sustainable development strategies and European integration processes requires the training of specialists engaged in sustainable development educational activities. Objectives. The study aimed to show the impact of the experimental methodological system on the forming the practical component of physical education for future physical education and sports specialists’ readiness for educational activities contributing to sustainable development. Materials and methods. The study involved 390 students from the faculties of physical education of the T. H. Shevchenko National University “Chernihiv Colehium”, the National University of Life and Environmental Sciences of Ukraine, Sumy State University, and Sumy State Pedagogical University named after A. S. Makarenko, future specialists in physical culture and sports. The students were informed about the features of the study and voluntarily participated in the pedagogical experiment. The participants of the study are represented by both sexes of different courses, from which the control and experimental groups were formed. The research methods used include the study and analysis of scientific and scientific-methodical literature, pedagogical experiments, surveys, testing, analyses, synthesis and generalisation of information, as well as methods of mathematical statistics. Results. At the beginning of the study, 93.33 % of students in the control group and 94.44 % of students in the experimental group had a low level of the practical component of readiness for educational activities contributing to sustainable development. The final stage of the study revealed a significant improvement in the studied indicator within the experimental group: 43.33 % of students demonstrated a low level of the practical component of the studied readiness, 16.67 % had a satisfactory level, 31.11 % showed an average level, and 8.89 % had a high level. The corresponding changes were observed in all defined indicators: activities for sustainable development in physical education classes or sectional sports lessons; activities for sustainable development during extracurricular work of a physical education teacher or outside the sectional work of a sports coach with a population of different age groups; and activities for sustainable development in managerial positions. In the control group, at the end of the experiment, no significant changes were found in the the practical component levels of future physical education and sports specialists’ readiness to participate in educational activities for sustainable development. Conclusions. The findings of the pedagogical experiment confirmed the positive impact of the developed methodological system on the forming the practical component of future physical culture and sports specialists’ readiness to participate in educational activities for sustainable development.